Correction: Selective CO production by Au coupled ZnTe/ZnO in the photoelectrochemical CO2 reduction system. Issue 3 (23rd December 2015) - Jang, Youn Jeong; Jang, Ji-Wook; Lee, Jaehyuk; Kim, Ju Hun; Kumagai, Hiromu; Lee, Jinwoo; Minegishi, Tsutomu; Kubota, Jun; Domen, Kazunari; Lee, Jae Sung
Abstract : Correction for 'Selective CO production by Au coupled ZnTe/ZnO in the photoelectrochemical CO2 reduction system' by Youn Jeong Jang et al., Energy Environ. Sci., 2015, 8, 3597–3604.